Parameter study of neck force in restrained 3 year old child involved in vehicle side impact - Shasthri, Sevaguru; Venkatason, Kausalyah; Shah, Qasim Hussain; Abdullah, Kassim Abdulrahman; Idres, Moumen; Wong , Sha Voon (AENSI Publisher, 2014)
Child casualties and fatalities due to motor vehicle crashes are an increasing concern. In side impact crashes, the investigation of neck forces pertaining to Child Restraint System design, misuse and crash parameters are yet unexplored due to modelling constraints and experimental limitations. In this work, a three year old child seated in a Child Restraint System is subjected to lateral side impact crash. A Prescribed Structural Motion simulation method is used in which the loading pulse is obtained based on experimental data. A hybrid model comprising of multi-body ellipsoids and finite elements is developed and validated for the simulation of the lateral side impact of a HYBRID III three year old child dummy. The model is found to be computationally very economical as well as acceptably accurate. Subsequently, the model is adapted to include intrusion effects at oblique impact angles and the Design of Experiments methodology is used as a tool for this purpose. A Latin Hypercube Sampling design is used to generate the simulation runs for which a total of six parameters are considered. The simulation runs are conducted with two different impact velocities and are grouped separately. The impact velocities used are 15 km/h and 20 km/h in which the former represents the standard test impact speed. The singular and cross interactive effect of each parameter on the Neck Force of the three year old child dummy is studied. This is achieved through regression analysis where the Response Surface Method models are shown to be suitable for the mathematical modelling of the problem. Student’s t test is used to conduct parameter sensitivity studies for the Neck Force response. The impact angle is revealed to be the most sensitive parameter to affect neck forces during side impact, especially for narrow impact angles (ϕ ≤ 60°). A critical range is established in which the Neck Forces are found to be highest primarily between impact angles 50° and 70°. A secondary critical range is also observed for angles below 34°. It is seen that most of the other parameters are generally found to be moderately significant only at low impact speed (15 mph).